Menafsir Ulang Keadilan: Epistemologi Emansipatif, Rekognisi Kontekstual, dan Kapabilitas Relasional: Reinterpreting Justice: Emancipatory Epistemology, Contextual Recognition, and Relational Capabilities - Andry, Muhammad Andry Mukmin (Undiksha, 2025)
This study proposes an alternative philosophical framework for understanding social justice in the context of Indonesia through three main pillars: emancipatory epistemology, contextual recognition, and relational capability. Starting with a critique of the dominance of technocratic and positivist approaches in poverty alleviation policies, this article rejects perspectives that reduce poverty to mere statistical figures. Emancipatory epistemology positions marginalized groups as subjects of knowledge, not merely objects of measurement. Contextual recognition emphasizes the importance of social acknowledgment rooted in local values and community ways of life. Meanwhile, relational capability revises Amartya Sen’s capability approach by asserting that individual well-being depends on social networks, power relations, and collective structures. These three concepts form the theoretical foundation for reinterpreting justice as a process that is situated, participatory, and committed to equity. This study also serves as a critique of the hegemony of universalistic policies that neglect the voices and experiences of local communities.